Characterizing the Fatigue Damage in a Martensitic Spring Steel. Issue 12 (19th August 2021) - Wildeis, Anna; Christ, Hans-Jürgen; Brandt, Robert; Thimm, Matthias; Fritzen, Claus-Peter
Abstract : Herein, a short crack propagation in a martensitic spring steel by means of in situ fatigue tests in a confocal laser microscope and additional electron back‐scattered diffraction analyses to link the local crystallographic orientation of the hierarchical martensitic microstructure with the short crack propagation behavior are investigated. For this purpose, different stress levels are imposed at a constant R ratio of −1 and a frequency of 10 Hz applying a sinusoidal command signal. It is found that the early fatigue damage evolution is characterized by the formation of slip bands, which subsequently serve as crack initiation sites. Most of the slip bands and correspondingly most of the short fatigue cracks initiate at or close to prior austenite grain boundaries. A strong dependence of the crack density, used as a parameter for fatigue damage, on the applied stress amplitude could be observed. The prior austenite grain boundaries can be identified to act as obstacles to short crack propagation because of the corresponding strong change in the crystallographic orientation, leading to an oscillating short crack propagation rate. Abstract : The fatigue damage evolution is characterized by the formation of numerous slip bands, which arise at or close to prior austenite grains and serve as crack initiation sites. Furthermore, the prior austenite grain boundaries act as obstacles to short crack propagation because of a strong change in the crystallographic orientation, leading to an oscillating short crack propagation rate.